INSTRUMEN DAN MEDIA DALAM LAYANAN BIMBINGAN DAN KONSELING DI MADRASAH - Aprilia, Lisnawati; Hartini, Hartini; Rizal, Syamsul (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2023)
Abstract: Instrument and media in guidance and counseling services aretools used in helping a counselor or psychiatrist in resolving the problems faced by the students or individuals, until the students’ problem or individuals can be resolved soon. Nowadays, the implementation of guidance and counseling servicescan be said that it has run in various level of education, such as: kindergarten, elementary school, junior high school, and senior high school. Although we can say that it has run, however the implementation has not been maximal yet. Because the implementation of guidance and counseling serviceshave not been maximal yet, the researcher was interested in discussing about the use of instrument and media in guidance and counseling services, including the instruments used are based on analysis of data and the needs of the students.Keywords: Instrumentand media, Guidance and Counseling Service.Abstrak: Instrumen dan media dalam layanan bimbingan dan konseling adalah alat yang digunakan dalam membantu seorang konselor atau psikiater dalam menyelesaikan permasalahan yang dihadapi oleh siswa atau individu, sehingga permasalahan siswa atau individu tersebut dapat segera terselesaikan. Saat ini penyelenggaraan layanan bimbingan dan konseling dapat dikatakan sudah berjalan di berbagai jenjang pendidikan, seperti: Taman Kanak-Kanak, Sekolah Dasar, Sekolah Menengah Pertama, dan Sekolah Menengah Atas. Meski bisa dikatakan sudah berjalan, namun implementasinya masih belum maksimal. Karena pelaksanaan layanan bimbingan dan konseling belum maksimal, maka peneliti tertarik untuk membahas tentang penggunaan instrumen dan media dalam layanan bimbingan dan konseling, termasuk instrumen yang digunakan berdasarkan analisis data dan kebutuhan siswa.Kata Kunci: Instrumen dan Media, Layanan Bimbingan dan Konseling.